CLINICAL-LABORATORY REMISSION IN A PATIENT WITH RHEUMATOID ARTHRITIS AFTER APPLICATION OF SYNCHRONIC PROGRAM INTENSIVE THERAPY (SPIT) - E A Aseyeva; S K Soloviev; A S Chiklikchi (Научно-практическая ревматология, 2001)
A clinical case of successful SPIT application in a patient with high RA activity was presented